A Survey of Cheese from Small-Scale Artisanal Producers in Western Cape, South Africa. (29th October 2021) - Nyamakwere, F.; Esposito, G.; Dzama, K.; Muller, M.; Moelich, E. I.; Raffrenato, E.
Abstract : The objective of this study was to assess cow milk cheese from small-scale producers in the Western Cape Province, South Africa. Forty cheeses were selected, and microbiological data of the samples were analyzed with age (1, 3, 6 months), cheese type (Cheddar, Gouda, other), and milk type (raw and pasteurized) as main factors. Rapid sensory characterization was done using the sorting technique. The results indicated that the available cheese types were diverse, with minority (20.0%) in the Gouda group followed by Cheddar (32.5%) and "other" (47.5%). Most of these cheeses (45%) were aged three months and produced using pasteurized milk (92.5%). Five cheese samples did not meet the European Union standards for coliforms, and four samples tested positive for Escherichia coli . Sensory analysis results showed a clear differentiation between mature and young cheese. In conclusion, the current market presents more diverse milder cheeses, and there is a need to follow proper hygiene protocols to reduce cross-contamination.